Correlation between Diabetic Retinopathy Severity and HbA1c Levels - Abdul Jabbar, Muhammad Yaqoob Khan, Momin Khan, Zia Ullah, Salman Khan, Fawad Ali, Fawad Khalid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetic retinopathy (DR) is an often-encountered disease complication of diabetes mellitus and a significant cause of blindness. Glycemic control, such as HbA1c levels, is vital in the development and progression of DR. Objective: The research is designed to determine the relationship between the degree of diabetic retinopathy and the extent of HbA1c in diabetic patients with type 2 diabetes. Methods: The proposed observational study was conducted at Medicine Department, Saidu Group of Teaching Hospital in the duration from November, 2022 to April, 2023. The number of patients registered was 150, and they had type 2 diabetes. HbA1c was determined, and the degree of retinopathy was determined by digital retinal imaging and the ETDRS grading scale. Pearson gave the correlation and regression analysis that was used to identify the dependence of HbA1c and the severity of DR. Results: There was a positive correlation between the severity of DR and the level of HbA1c (r = 0.68, p = 0.01). The HbA1c level was observed to correlate with more severe retinopathy, including proliferative diabetic retinopathy. Conclusion: Diabetic retinopathy management has an essential role in the mechanism of disease prevention by means of glycemic control. The HbA1c level monitoring and early screening should be part of the DR risk management. Keywords: Diabetic retinopathy, HbA1c, type 2 diabetes, glycemic control, severity, correlation.